Rasm Utsmani dalam Al-Qur’an Indonesia pada Kelompok Pemuda Amor (Arek Mor Lorong) Kecamatan Lenteng Sumenep - Khairul Muttaqin; Jamal Abd. Nasir (IAIN Madura, 2019)
The Ottoman rasm was the method of writing agreed upon by the companions of the Prophet Muhammad in codifying the Qur'an which was feared lost and destroyed if it was not immediately codified. The Qur'an at that time was written without adding vowel and letter dots in the writing. However, the The companions of prophet MUHAMMAD SAW can read it because of the Arabic fluency of the companions and a high level of memorization. Over time the writing of the Koran began to add vowel and letter dots because generations after the companions found it difficult to read the Koran without punctuation such as vowel and dots on the letter. The al-Qur'an published by the Ministry of Religion of the Republic of Indonesia has experienced many improvements in its writing, but there are ways of writing the Ottoman Manuscripts that are still contained in the Qur'an published by the Ministry of Religion of the Republic of Indonesia. This can cause errors if not explained how to read it. Because of that, community service was carried out about the Ottoman rasm in the Qur'an. The target group for community service activities is the youth group AMOR (Arek Mor Lorong) Lenteng Sumenep. The target group does not yet have the knowledge and skills to read the Ottoman rasm written in the Indonesian Qur'an. Therefore, in this community service activity, material about Ottoman rasm was delivered in the Indonesian Qur'an. As a result, the youth group AMOR (Arek Mor Lorong) Lenteng Sumenep finally gained in-depth knowledge about the Ottoman rasm found in the Indonesian Qur'an.